Bitcoins in the Malaysian Economy - Miraz, Mahadi Hasan; Mohd Sharif, Kamal Imran; Hassan, Mohamad Ghozali; Ismail, Mohd Azril; Ahmad Mahyadin@Mahidin, Fariza (Paragon International University in Cambodia, 2021)
Bitcoin is digital money, and it is public and distributed in its ecosystem. A bitcoin first released by Satoshi Nakamoto in 2008. It is a peer-to-peer (direct connections without an intermediary), open-source encryption system, where transactions occur through a public directory called a blockchain. However, bitcoin has no proper review in the Malaysian context. Also, there is no specific and descriptive analysis of bitcoin in Malaysia. Though Bitcoins have already gained widespread popularity worldwide, it would be better to control this industry through proper management. The faster it is, the more accessible. However, blockchain technology is redeeming in a positive light. This study focused on individual facts and details, such as articles, reviews, forums, Malaysians brochure, business lines, and research reports. The study relies on secondary data. This study's primary aim to review previously studied that focuses on bitcoin around the globe and Malaysia. A method of meta-analysis is used for theory-building. This study provides the Malaysian bitcoin market’s key insights and understing to consumer and operator.Therefore conclude with a summarization of bitcoin's current situation in Malaysia